Alterations in Expression Pattern of Splicing Factors in Epithelial Ovarian Cancer and its Clinical Impact. Issue 6 (1st July 2013) - Iborra, Severine; Hirschfeld, Marc; Jaeger, Markus; zur Hausen, Axel; Braicu, Iona; Sehouli, Jalid; Gitsch, Gerald; Stickeler, Elmar
Abstract : Objective: Alternative splicing represents an important nuclear mechanism in the posttranscriptional regulation of gene expression, which is frequently altered during tumorigenesis. Previously, we described marked changes in alternative splicing of the CD44 gene in ovarian and breast cancer as well as specific induction of distinct splicing factors during tumor development. The present study was focused on the expression profiles of different splicing factors, including classical serine-arginine (SR) proteins including ASF/SF2, hTra2β1, hTra2α, and Y-box–binding protein (YB-1) in physiological and malignant epithelial ovarian tissue to evaluate their expression pattern with regard to tumor development and disease progression. Materials and Methods: Expression levels of the different splicing factors were analyzed in physiological epithelial ovarian tissue samples, primary tumors, and metastatic samples of patients with a diagnosis of epithelial ovarian cancer using quantified reverse transcription polymerase chain reaction analysis. We examined more closely the splicing factor hTra2β1 using Western blot analysis and immunohistochemistry. Results: The analysis revealed a marked and specific induction of ASF/SF2, SRp20, hTra2β1, and YB-1 in primary tumors as well as in their metastatic sites. However, in our patient cohort, no induction was seen for the other investigated splicing factors SRp55, SRp40, and hTra2α. Conclusions: Our results suggest a specific induction of distinct splicing factors in ovarian cancer tumorigenesis. The involvement of hTra2β1, YB-1, SRp20, and ASF/SF2 in exon recognition and alternative splicing may be important for gene regulation of alternatively spliced genes like CD44 with potential functional consequences in this tumor type leading to progression and metastasis.